The understanding of peace in a culturea case study of Sundanese worldview in building peace and its analysis from the Qur‘ānic perspective - Rashid, Ungaran (IIUM Press, 2022)
Living in peace is, perhaps, a term or a situation that is longed for by every community in the world. Living in peace may mean to live in a harmonious life, to be secure and prosperous, and/or to love one another in a community. In many cultures in the world, people can find the concept of peace, such as in language, worldview, art and others. However, the owners of these cultures forget that they have that notion in their life. Thus, in many conflict issues, people in conflict within a particular culture often seek a third party to be a mediator. Unfortunately, the peacemaker is often brought in from outside their culture, so efforts to build peace often fail because they do not understand the root causes of the conflicting parties. In this article, the researcher examines the concept of peace in Sundanese worldview as a case study to explore the concept of peace in a culture. The concept of peace has existed and has been a valued aspect of Sundanese culture throughout history, even before Islam came to Parahyangan (Sundanese lands). Various aspects of peace, such as non-violence, tolerance and forgiveness, are evident, even though only informally, and have been passed on from generation to generation within families and the wider community. Besides, the researcher attempts to investigate whether the concept of peace that exists within Sundanese worldview is in accord with that described in the Qur’ān. The data for this study were gathered primarily through participant observation and library research. The resources of the library research are used to observe the concept of peace from two sources: Sundanese culture and Qur’ānic perspectives.